Foreign direct investment and sustainable economic development challenges in Iraq for the Period (2003–2025) - Iqbal Hashim Al-Lami (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial, 2026)
Few economic puzzles in the developing world are as startling as that of Iraq: a country that has lured hundreds of millions of dollars in foreign investment for two decades, yet where the jobless rate has stubbornly refused to drop below fifteen percent. Figures cannot lie but they may point toward a larger problem that total influx numbers cannot reveal. This essay is based on the paradox and will endeavor to pursue it in an orderly fashion over the years from 2003 to 2025. The paper integrated a story-telling account on the simultaneous or independent variations of investment and unemployment with certain formal econometric tests meant to clarify their relationship. It is not about poverty. Iraq has had the money. The problem is that the revenue it has collected has been channeled mostly into a single sector͏ - oil - which does not create many jobs for Iraqi people, repatriates its profits abroad and shows no interest in developing infrastructure or labor relations that might result in widespread employment. The following results attempt to measure this difference and draw a few concrete policy implications.